A wideband slot antenna for mobile phone applications - Xia Xiao; Wei-Hua Zong; Shan-Dong Li; Xiang-Yang Wei; Xiao-Yun Qu (2016 IEEE 5th Asia-Pacific Conference on Antennas and Propagation (APCAP), 2016)
A slot antenna configuration is proposed to enhance the bandwidth at lower band of mobile communication. The slot is composed of two rectangles forming L shape. The antenna is fed by a 50 Ω microstrip connected to a U-shaped strip. A C-shaped strip is mounted vertically to the circuit board. The measured -6dB bandwidth of the proposed antenna covers 0.69-0.98 GHz, 2.19-3.36 GHz, and 4.03-5GHz.